Human-tech ethical and scientific foundations - Vicente, Kim J.; Kirlik, Alex. (New York ; Oxford : Oxford University Press, 2011)
The articles collected in this book provide much of the technical material behind the work that was presented in 'The Human Factor', and the commentaries by Alex Kirlik situate these articles in their broader historical, scientific and ethical context.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Human-computer interaction; Information technology -- Moral and ethical aspects